Conditions for the formation of traps and oil and gas deposits in Western Turkmenistan - U. S. Serikova; M. A. Allanazarova; E. S. Nyrenberg (Известия высших учебных заведений: Геология и разведка)
Introduction. The study of the conditions for the development of discontinuous disturbances makes it possible to draw conclusions that in the formation and destruction of various deposits, they are connected by discontinuities different in the mechanism of their formation. The lithological composition of the rocks in contact with it has a certain significance for assessing these gaps in relation to the formation or disbandment of deposits. The main role here is played mainly by clay sections, the material of which fills the cracks, preventing the destruction of hydrocarbon deposits in individual suites (Middle Pliocene deposits).Aim. Identification of conditions for the formation of traps and deposits of oil and gas within western Turkmenistan.Materials and methods. Analysis of published literature and factual data.Results. Thus, discontinuous disturbances are the most important factor in the formation of deposits and play an exclusively creative role, forming oil deposits of a tectonically shielded type.